City of secrets [large type] - O'Nan, Stewart, 1961- (Center Point Large Print, 2016)
In 1945, Jewish refugees by the thousands set out for Palestine. Those who made it relied on the underground to shelter them; taking false names, they blended with the population, joining the wildly different factions fighting for independence. Brand is trying to regain himself after losing everyone he's ever loved. Now driving a taxi provided-- like his new identity-- by the underground, he navigates the twisting streets of Jerusalem as well as the overlapping, sometimes deadly loyalties of the resistance. Trying to become again the man he was before the war he falls in love with Eva, a fellow survivor and member of his cell, and commits himself to the revolution. As his missions grow more dangerous, he suspects he's being used by his cell's leader, Asher.